(untitled) (Bangladesh Journal of Zoology, 2015)
A male Bhamo frog Humerana humeralis was first time collected from Rangpur, Bangladesh, outside its usually habitat. The dorsal surface was characteristically olive brown to bright green in colour and the ventral surface was whitish. Black spots were distributed between nostril and between eyes. The length of snout-vent, head, snout were found to be 43.25 mm, 14.50 mm and 7.5 mm, respectively. Some information of its natural history is also included in the paper. Bangladesh J. Zool. 42(2): 277-282, 2014